2023
DOI: 10.3390/toxics11070581
|View full text |Cite
|
Sign up to set email alerts
|

Time- and Concentration-Dependent Adverse Effects of Paclitaxel on Non-Neuronal Cells in Rat Primary Dorsal Root Ganglia

Abstract: Paclitaxel is a chemotherapeutic agent used to treat a wide range of malignant tumors. Although it has anti-tumoral properties, paclitaxel also shows significant adverse effects on the peripheral nervous system, causing peripheral neuropathy. Paclitaxel has previously been shown to exert direct neurotoxic effects on primary DRG neurons. However, little is known about paclitaxel’s effects on non-neuronal DRG cells. They provide mechanical and metabolic support and influence neuronal signaling. In the present st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 87 publications
1
0
0
Order By: Relevance
“…NC2 had a good toxicity profile up to the 10 µM dose, and then the viability of the fibroblasts dropped below the 70% threshold. When measuring the cytotoxicity of the compounds on neurons, our data showed that PTX had a toxic effect on the viability of the cells in a time-dependent manner but concentration-dependent for only the 10 µM dosage, in line with similar studies ( Guo et al, 2017 ; Elfarnawany and Dehghani, 2022 ; Elfarnawany and Dehghani, 2023 ). However, when PTX was combined with the cannabinoids, the percentage of cytotoxicity decreased, suggesting a protective role that cannabinoids have for preserving neurons.…”
Section: Discussionsupporting
confidence: 89%
“…NC2 had a good toxicity profile up to the 10 µM dose, and then the viability of the fibroblasts dropped below the 70% threshold. When measuring the cytotoxicity of the compounds on neurons, our data showed that PTX had a toxic effect on the viability of the cells in a time-dependent manner but concentration-dependent for only the 10 µM dosage, in line with similar studies ( Guo et al, 2017 ; Elfarnawany and Dehghani, 2022 ; Elfarnawany and Dehghani, 2023 ). However, when PTX was combined with the cannabinoids, the percentage of cytotoxicity decreased, suggesting a protective role that cannabinoids have for preserving neurons.…”
Section: Discussionsupporting
confidence: 89%